Dosimetry of Various Human Bodies Exposed to Microwave Broadband Electromagnetic Pulses - Chakarothai, Jerdvisanop; Wake, Kanako; Fujii, Katsumi (Frontiers in Public Health, 2021)
In this paper, human exposures to ultra-wideband (UWB) electromagnetic (EM) pulses in the microwave region is assessed using a frequency-dependent FDTD scheme previously proposed by the authors. Complex permittivity functions of all biological tissues used in the numerical analyses are accurately expressed by the four-term Cole–Cole model. In our method, we apply the fast inverse Laplace transform to determine the time-domain impulse response, utilize the Prony method to find the Z-domain representation, and extract residues and poles for use in the FDTD formulation. Update equations for the electric field are then derived via the Z-transformation. Firstly, we perform reflection and transmission analyses of a multilayer composed of six different biological tissues and then confirm the validity of the proposed method by comparison with analytical results. Finally, numerical dosimetry of various human bodies exposed to EM pulses from the front in the microwave frequency range is performed, and the specific energy absorption is evaluated and compared with that prescribed in international guidelines.